Ipsilateral breast metastasis after axillary dissection caused by epithelioid sarcoma: a case report and pathological investigation - Luyan Chen; Li Wang; Xiaochen Zhang; Minya Yao; Peifen Fu (BMC, 2019)
Abstract Background Epithelioid sarcoma (ES) is a rare malignant soft tissue tumor, commonly occurring in distal extremities, such as fingers, hands and wrists. For oncologists and surgeons, a female patient with enlarged axillary lymph node on one side only is easily diagnosed with an occult breast carcinoma rather than ES. Besides, whole breast metastasis of ES has not been reported yet. Case presentation A 47-year-old Chinese woman came to the outpatient clinic of First Affiliated Hospital of Zhejiang University (FAHZU) with a complaint of an asymptomatic right axillary mass for 3 months. Then she received surgical resection of the right axillary lymph nodes and right supraclavicular lymph nodes. According to the clinical tumor site and routine immunohistochemistry (IHC), suspicion of metastatic epithelial sarcoma and metastatic breast cancer could not be ruled out. Subsequently, with more detailed medical history review and physical examination, a mass on the right forearm was found, which was considered as the primary lesion. Further IHC and Molecular Genetics revealed that all the neoplastic cells exhibited loss of INI1 protein and were negative for ERG gene rearrangement yet positive for epithelial membrane antigen (EMA), cytokeratin (CK) 8, CK19, Vimentin, CD34. The final diagnosis was ES. She received postoperative chemotherapy, without radiotherapy. Unexpectedly, an ipsilateral breast metastasis was developed at ten months after surgery. Regrettably, there was no positive result of the metastatic breast sample, based on a genome sequencing by a 381-cancer-gene panel in a lab. Therefore, she went through another round of chemotherapy and took Apatinib for maintenance treatment. During the last follow-up (26 months after diagnosis), the disease was under control. Conclusion This rare but interesting case enables breast surgeons and pathologists to accumulate more experience of differential diagnosis of axillary mass for personalized treatment in clinical practice. Meanwhile, ipsilateral breast metastasis of ES we reported in the case urges that clinicians attach greater importance to the tumor metastasis mechanism.